Assessing the Impact of Parents’ Adolescent Reproductive and Sexual Health Knowledge on Sexual Health Education by Parents in the Asutifi (North and South) Districts of Ghana - Adjei, Evelyn Serwaa; Baah, Kennedy Ameyaw (International Journal of Scientific Research and Management (IJSRM), 2020)
Parent’s involvement in adolescent sexual health education has been identified as one of the effective ways of reducing sexual risk behaviour among adolescents. However, a number of factors may prevent parents from carrying out adolescent sexual health education. Four hundred and twenty-four (424) parents/guardians, including 180 males and 244 females were randomly selected from the Asutifi north and south districts of the Brong- Ahafo region of Ghana for the cross- sectional study. Self-administered and interviewer-administered questionnaires consisting of demographic characteristics, parent’s knowledge on adolescent sexual health, socioeconomic factors, cultural factors and practice of sexual health education were the measures for the study. Literate respondents had self-administered questionnaire while illiterate respondents had interviewer administered questionnaires. Interviewers translated the questionnaire from the English language to the local language (Twi) for illiterate respondents to ensure better understanding of the questions. 86.1% of the surveyed parents practice adolescent sexual health education. Females as well as married parents were found to practice sexual health education (SHE) more than male and unmarried parents respectively. Two variables remained significant after controlling for relevant demographic and other factors. These included parent’s knowledges on adolescent sexual health (OR=2.35; 95% CI 1.34-4.09) and parents’ level of education (OR= 3.47; 95% CI 1.27-9.45). Government agencies in collaboration with stake holders should develop policies that will ensure that parents are given the necessary training that will boost both their level of education and knowledge on adolescent sexual health.